Euprepes chaperi Vaillant, 1884, a junior subjective synonym of Mochlus guineensis (W. Peters, 1879) (Scincidae, Lygosominae) - Ineich, Ivan; Trape, Jean-François (Zootaxa, 2017)
During travel made in February and March 1882 in the former French Protectorate of Côte d’Or (southeastern Ivory Coast), Mr Chaper, who had previously sent numerous specimens to the Paris Natural History Museum (Muséum national d’Histoire naturelle, Reptiles & Amphibiens; MNHN-RA), collected about 19 reptiles (and one python egg) belonging to 12 species. All those specimens were deposited in the MNHN-RA collections. Among them some specimens were described as a new species, Euprepes chaperi, in two separate publications reporting on that collection published in the same year by Vaillant (1884a,b), head of the Zoology (Reptiles and Fishes) Laboratory at Paris Natural History Museum. The status of that species was not recently reviewed and several options are reported in literature including validity of the species (in the genus Lygosoma Hardwicke & Gray) or synonymy, sometimes simultaneously in the same data base (see Uetz & Hosek, 2016). We here locate the type series of E. chaperi and carefully check their identity.